Effect of calcium hypochlorite on surface sterilization and seedling growth of Vietnamese coconut varieties - Phuong Quynh, Tran; Lan Xuan, Hoang Thi; Ai My, Tran; Thanh Thao, Nguyen; Phuong Thao, Nguyen; Thien Quang, Nguyen (Vietnam Journal of Biotechnology, 2022)
Coconut (Cocos nucifera L.) or ’the tree of life’ is one of the most important palm crops due to its versatility. Reduction in coconut productivity due to natural calamity and disease threats has raised the urgent need to develop in vitro techniques that can overcome the obstacles of the traditional breeding method. Embryo culture is one of the earliest in vitro culture techniques applied to practical problems and so far has proved itself to be of great value to breeders. However, contamination is one of the most serious problems that reduces the efficiency in in vitro culture techniques. Thus, appropriate surface sterilization treatments are highly important to in vitro culture establishment. The present study was performed to evaluate the sterilization effect of calcium hypochlorite by comparing with sodium hypochlorite. This study also examined the effects of calcium hypochlorite concentrations on plantlets morphogenesis. The findings revealed that amongst the tested treatments, 0.5% (w/v) calcium hypochlorite was the most effective treatment with the lowest rate of contamination. This treatment also significantly improved shoot and root elongation in comparison with calcium hypochlorite at higher concentrations (3% and 6%, w/v). Thus, this concentration was found to be optimal for surface sterilization of two coconut cultivars - Aromatic and Xiem Red Dwarf. Besides that, the results obtained from this study indicated that 70% (v/v) ethanol was not critical in surface sterilization protocol of coconut embryo culture. This research has provided an improved approach for surface sterilization which was previously dependent on sodium hypochlorite and ethanol.